الاثار الفقهية المترتبة على تصرفات السفيه - جاسم، محمد كاظم (الجمعية العلمية للدراسات التربوية المستدامة, 2020)
في طيات هذا البحث المتواضع الذي اقدمه لكم جعلته من مقدمة ومبحثين، تناولت في المقدمة أهمية الموضوع وسبب اختياري له وفي المبحث الأول عرفت السفيه في القرآن الكريم وجعلته على ست مطالب وفي كل مطلب جعلته ضمن آية تتكلم عن السفيه في المطلب الأول بينت فيه مفهوم السفيه من حيث اللغة والاصطلاح وسردت أقوال الفقهاء والمفسرين في معنى السفيه وفي المطلب الثاني ما المراد بالسفيه في قوله تعالى عز وجل: (فَإِنْ كَانَ الَّذِي عَلَيْهِ الْحَقُّ سَفِيهًا)، بينت فيه أقوال الفقهاء والمفسرين والمطلب الثالث ما المراد بقوله عز وجل: (أَوْ ضَعِيفًا) والمطلب الرابع ما المراد بقوله عز وجل: (لَا يَسْتَطِيعُ أَنْ يُمِلَّ هُوَ) والمطلب الخامس تحديد القران الكريم السفهاء في قوله عز وجل: (وَلَا تُؤْتُوا السُّفَهَاءَ أَمْوَالَكُمُ) والمطلب السادس تعيين المخاطبين بقوله عز وجل: (وَلَا تُؤْتُوا السُّفَهَاءَ أَمْوَالَكُمُ). والمبحث الثاني يتكون من خمس مطالب لكل مطلب استقلاليته من حيث العنوان حيث عرفت الحجر والشروط التي يضعها الحاكم على المحجور بالسفه والولاية على السفيه وبينت كيف يعمل الوالي على السفيه ومتى يكون وقت زوال الحجر على السفيه ثم بينت أثر الأحكام في توفير حقوق السفيه مثل حقوقه من النكاح وحقوقه من الطلاق ومن البيع ما يصح بيعه وما لا يصح وهل تصح وصيته أو لا تصح وكذلك الهبة هل تصح هبته أو لا.
Summary of the research In the folds of this humble research that I present to you, I made it from an introduction and two topics. In the introduction, I discussed the importance of the topic and an optional reason for it. Foolishness in terms of language and terminology, and I have mentioned the sayings of jurists and interpreters in the meaning of foolishness and in the second requirement, what is meant by foolishness in the Almighty saying no (if it is the one who has the right to it, I have stated in it the sayings of jurists and interpreters and the third requirement is what is meant by saying to: and or put it) and the fourth requirement is what is meant His saying n: (Or he cannot fulfill it and the fifth requirement determines the Holy Qur’an the foolish in his saying: (And do not pay fools money and the sixth requirement is the appointment of the addressees by saying: (And do not harbor your money. The second topic consists of five demands for each of its independence requirements in terms of the address where you know The stone and conditions that the ruler places on the yearly quarantined, guardianship over fools and House W On foolishness, and when the time for the removal of the stone is on foolishness, then I showed an effect on foolishness, such as his rights to marry and his rights to divorce and from selling. What is valid: His will is valid or not valid, as well as the gift. Is his gift valid or not.
Keywords: القرآن الكريم -- الفقه الإسلامي -- الأحكام الشرعية